Grab 'n' go astronomy - English, Neil (The Patrick Moore Practical Astronomy Series,, 2014)
Like everyone else, most amateur astronomers live busy lives. After a long day, the last thing you want as an observer is to have to lug out a large telescope and spend an hour getting it ready before it can be used. Maybe you are going somewhere sure to have dark skies, but you don't necessarily want astronomy to dominate the trip. Or you are not quite committed to owning a large telescope, but curious enough to see what a smaller, portable setup can accomplish. These are times when a small "grab 'n' go" telescope, or even a pair of binoculars, is the ideal instrument. And this book can guide you in choosing and best utilizing that equipment.   What makes a telescope fall into the "grab 'n' go" category? That's easy - speed of setting up, ease of use, and above all, portability. This ambitious text is dedicated to those who love to or - because of their limited time - must observe the sky at a moment's notice. Whether observing from the comfort of a backyard or while on business or vacation far from home, everything you need to know is here. So get started!!     -          Surveys the pros and cons of the various types of equipment, including accessories and mounts, that are available.   -          Advises how to use your grab 'n' go telescope to visit a wealth and wide variety of objects, from solar, lunar and planetary observing to hunting deep sky objects of all kinds.